Penerapan E-LKPD Interaktif dengan Pendekatan Studi Kasus untuk Meningkatkan Pemahaman Dampak Sosial Informatika di SMP: Penelitian - Putri Alivia Nabila; Syaad Patmanthara; Rachman Kurniawan; Lailatussa’adah; Rahmadita Sugma Ryanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The purpose of this study was to develop and test the success of implementing an interactive Student Worksheet (e-LKPD) based on case studies in learning the Social Impact of Informatics (DSI) in junior high schools. This study implemented Classroom Action Research (CAR) in two cycles. Each cycle included planning, implementation, observation, and reflection. The subjects were 31 students of class VII A at SMP Negeri 8 Malang. The results showed that the use of e-LKPD based on case studies can improve students' understanding of the social impact of informatics, especially in differentiating personal and private information, as well as applying ethical principles and privacy laws. In the first cycle, the percentage of students who completed the learning reached 70.97%, and the average student score increased to 82.42. After improvements were made in the second cycle, the percentage of students who completed the learning increased to 80.65%, with an average score reaching 86.57. This improvement indicates that the integrated case study approach in e-LKPD can encourage students to be more involved in discussions and develop critical thinking skills regarding social issues related to digital technology. This research provides an important contribution to the development of more contextual and interactive informatics learning, and can be used as a reference to improve the quality of learning at the junior high school level.